INOVASI INTEGRITAS QR CODE INFORMASI DAN EDUKASI SEKOLAH DASAR SDN 138/IV KOTA JAMBI - Safitri, Eca; Novita Handayani, Pahlipi; Faska Ayu, Yuni; Faradila Eka Fitri, Regita; Maharani, Sintia; Sry Wahyuni, Endang; Destrinelly; Syarif, Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop a school website integrated with QR Code as an information and education at SDN 138/IV Kota Jambi. The research employed the Research and Development (R&D) method using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The developed product was a school website integrated with QR Code to facilitate access to school information and support digital-based educational services. Data were collected through observation, interviews, validation questionnaires, and user response questionnaires. The subjects involved vice principal, school operator, media expert, and language expert. The validation results showed that the product obtained a score of 92.5% from media experts and 94.2% from language experts, both categorized as very valid. The implementation stage included training for school operators to independently manage website content and the application of QR Codes on school information media. User responses showed a practicality score of 91.6% categorized as very practical. The effectiveness evaluation indicated that the website and QR Code improved access to school information and increased the number of new student registrations from 23 to 30 students. Therefore, the school website integrated with QR Code is proven to be valid, practical, and effective as a medium for information, education, and school promotion. This innovation supports the digital transformation of education and improves the quality of information services in elementary schools.